Multi-channel supply chain optimisation in cyber-physical environment under quantity discounts - Bányai, Ágota; Efimenko, Dmitry; Béla, Illés; Tamás, Peter; Bányai, Tamás (Journal of Production Engineering, 2020)
The procurement, manufacturing, distribution, and recycling processes within the circular economy have undergone significant changes. The increasing complexity of these processes has necessitated the application of new models, methods, tools, and technologies. Multi- and omni-channel purchasing and distribution solutions have introduced new challenges for researchers, prompting the exploration of novel models and algorithms to support the optimal design and operation of these processes. In this article, the authors present a mathematical model of a multi-channel supply chain solution within a cyber-physical environment, where the purchasing processes involving suppliers and customers are integrated within a supply chain cloud. Numerical analysis is conducted to validate the described model.